Pengaruh Pemberian Berbagai Konsentrasi Pupuk Organik Cair Dari Urine Kambing Terhadap Pertumbuhan Bibit Tanaman Pinang (Areca Catechu, L.) - Juliyansyah, Juliyansyah; Muliani, Muliani; Yama, Danie Indra (Perkebunan dan Lahan Tropika, 2023)
The Effect Of Various Concentrations Of Liquid Organic Fertilizer From Goat's Urine On The Growth Of Growth Of Areca Plants (Areca Catechu, L.).  Betel palm (Areca Catechu, L.) is one of the plants that has various benefits ranging from health, care, to coloring. The purpose of the study was to determine the effect of giving goat urine liquid organic fertilizer on the growth of areca nut plants. This study used a non-factorial randomized block design (RAK), with 5 treatment concentrations and replicating 4 times, namely: Po: 0% (0 ml poc + 1000 ml water), P1: 5.0% (50 ml poc + 950 ml water), P2 : 10% (100 ml poc + 900 ml water), P3 : 15% (150 ml poc + 850 ml water), P4 : 20% (200 ml poc + 800 ml water), with fertilizer spray method liquid organic as much as 50 ml/plant every 1 week. Parameters observed were plant height (cm), number of leaves (strands), stem diameter (mm). The results of this study showed that giving urine liquid organic fertilizer for P1 treatment had a significant effect on the number of leaves at 5 Mst, namely 2.10 leaves.